Oral Health Status and Quality of Life Among Rohingya Refugee- A Cross Sectional Study at Kelambakkam, Chennai: Life Science-Public health - M, Anita.; Srinivasan, T.G.; Sruthi, K G; Balasubramaniam, Arthi (International Journal of Life Science and Pharma Research, 2022)
The Rohingya people are a minority who live mainly in northern Rakhine State (formerly Arakan) in Myanmar and are said to be one of the most persecuted ethnic minorities in the world. They describe themselves as descendants of Arab merchants who settled in the area many generations ago. They have been persecuted in their home state of Rakhine in Myanmar because they deny citizenship. They have crossed the border into neighboring countries, including Bangladesh, for escaping extreme violence against ethnic and religious minorities, where about a million people reside. reside in Cox's Bazar district. Refugee camps are overcrowded with poor sanitation, meaning they pose a health risk, and dental health is no exception and is often overlooked. Oral health professionals are unable to deal with these deal problems due to their different cultures. The article aims to assess oral health status and quality of life among Rohingya refugees in Kelambakkam, Chennai. An operated administered pre-tested questionnaire specially designed for this purpose was used. Demographic information, Dentition status, Periodontal Status of adults and children were recorded for the Rohingya Refugee at Kelambakkam, Chennai. Caries prevalence was found to be 84.8% among adults aged 15 years and above. Periodontal disease with gingival bleeding was present among 57.6%. Caries prevalence was found to be 50% among children under the age of 15 years. Gingival bleeding was found to be highly significantly correlated with functional limitation, physical pain, and psychological discomfort. The most common dental problems were gingival or periodontal problems, dental caries, and decayed teeth, highlighting the need for a comprehensive dental care program. However, the Government should take more measures to advocate dental health policies and treatment of refugees and implement strategies